Hubungan Dukungan Keluarga dengan Kenakalan Remaja di SMK N 1 Padang Tahun 2024 - Firda Damba Wahyuni; Ira Sri Budiarti (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2024)
Juvenile delinquency is currently increasing. Data from the West Sumatra Education Office has the highest prevalence of juvenile delinquencyat almost70%, ranking second after brawls between students. The purpose of this study was to the relationship betwen family support with juvenile delinquency at SMKN 1 Padang.This research was conducted with quantitative methods. The research was conducted at SMK N 1 Padang in February-mart 2024. The research population was 1,017 students in grades 1 and 2. The sampling technique is proportional random sampling with a total sample of 91 students.The results showed more than half (53.8) juvenile delinquency occurred,morethan half (64.8%) family support were not concerned, more thanhalf (61.5%) There is a significant relationship between family support pv=0.002. It is hoped that it will be even more enhanced to makeregulations that can preventteenagers from doing things thatarenotgood suchas truancy, brawls andtighteningdisciplinemore, givingsanctions to those who break the rules such as summoning parents of teenagers who have problems and as well as teacher sanctions to prevent them no mischief occurred. Keywords: Juvenile Delinquenc;,family support